2005
DOI: 10.1109/lawp.2005.854004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a smaller unit cell planar EBG structure on the mutual coupling of a printed dipole array

Abstract: Abstract-A new smaller unit-cell planar electromagnetic bandgap (EBG) structure is proposed on low dielectric constant low-cost substrate (TMM: r = 4 5 thickness = 25 mils) that has a stopband frequency at around 4 GHz. The proposed structure when placed in between a two-element printed dipole array results in over 13-dB reduction in mutual coupling and a significant improvement in antenna return loss bandwidth and gain pattern.Index Terms-Antenna array, mutual coupling, planar electromagnetic bandgap (EBG), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…Reported other studies showed mutual coupling reduction by −13 dB at 4.18 GHz [16] and 20.5 dB at 12.2 GHz with two different uni-planar EBG arrays [34], and approximately 4 dB at 5.2 GHz with different shapes (H, I, X etc.) of planar designs [35].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Reported other studies showed mutual coupling reduction by −13 dB at 4.18 GHz [16] and 20.5 dB at 12.2 GHz with two different uni-planar EBG arrays [34], and approximately 4 dB at 5.2 GHz with different shapes (H, I, X etc.) of planar designs [35].…”
Section: Introductionmentioning
confidence: 83%
“…The coupling depends on the element separation and their orientation which causes scan blindness and forms blind spots. By increasing the element separation, mutual coupling can be lessened, but this would introduce undesirable grating lobes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that if the antenna size is larger than the proposed spiral PIFA or that if the antennas are placed much closer to each other or both, then the isolation will degrade. To solve such a problem, one may introduce slits on the ground plane [9] or use engineered structures [10] if the design scenario permits such adjustments.…”
Section: A S-parameters and Radiation Patternsmentioning
confidence: 99%
“…16. Similar tag antenna can also be designed based on the EBG structure (Abedin & Ali, 2005aYang & Rahmat-Samii, 2003) like the tag antenna shown in Fig. 12.…”
Section: Tag Antenna Mountable On Metallic Objectsmentioning
confidence: 99%